Effect of Quality Feeds and Litter Materials on Broiler Performance under Hot Humid Climate - Sharnam, Kumar Shambhu; Wadhwani, K.N.; Khanna, K.; Patel, A.M. (International Journal of Poultry Science, 2007)
Eight hundred eighty seven straight run day old commercial broiler chicks (Cobb) were randomly housed into eight equally spaced compartments (1.13 sq ft/bird) and allotted to two different rations viz. Ration-I: R1 (Broiler starter-I: 24.18% CP and 2999Kcal/Kg ME and Broiler finisher-I: 22.22% CP and 3108 Kcal/Kg ME) and Ration-II: R2 (Broiler starter-II: 22.12% CP, 2879Kcal/Kg ME and Broiler finisher-II: 19.87% CP and 2941Kcal/Kg ME) and two litter materials viz. L1 (Rice husk) and L2 (Wheat straw+saw dust) used and form four combinations in two replications viz. L1 R1, L1R2, L2R1 and L2R2. The body weight gain (g/bird) of experiment birds was recorded to be 1597.28 ± 34.66, 1595.10 ± 32.65, 1611.12 ± 34.66 and 1581.26 ± 32.65 under R1, R2, L1 and L2, respectively and influenced significantly by age only. Average weekly total feed intake (g/bird), FCR (Kg/Kg gain), average weekly water intake (ml/bird), water: feed intake ratio and performance efficiency factor were 512.50 ± 6.54, 1.59 ± 0.14, 1525.10 ± 25.08, 2.80 ± 0.08 and 212.10 ± 27.18, respectively and influenced significantly by age. The feed cost (Rs/bird) was 26.23 ± 0.07 and 26.43 ± 0.06 with R1 and R2, which did not influenced either by feed or litter materials but influenced significantly by their interaction. However, feed cost per kg gain (Rs/Kg), feed cost per dressed weight (Rs/kg), total production cost (Rs) on Ration I was 16.32 ± 1.88, 28.31 ± 0.29 and 18692.15 ± 36.98, respectively and were significantly higher than Ration II (15.22 ± 1.66, 25.69 ± 0.14 and 17642.76 ± 17.05) where as net profit/bird (Rs. 4.46 ± 0.08 and 8.45 ± 0.68), return over feed cost (Rs. 9461.86 ± 0.35 and 11347.96 ± 2.65) and return as percent of feed cost (184.44 ± 0.04 and 206.76 ± 0.02) were significantly lower in Ration I than Ration II. The litter materials showed their significant effect on average weekly livability percentage and manurial value. Ambient temperature inside the house was significantly higher than out side the house and established significant negative relationship with Relative Humidity (RH), Temperature Humidity Index (THI) and feed intake and significant positive relationship with water and water: feed intake ratio. The broiler birds can be reared economically on rice husk as a liter material by feeding 2879 (BS)-2941 (BF) ME energy and 22.12% (BS)-19.87% (BF) protein ration to harvest significantly higher return over feed cost (206.76%)